Potential mechanisms underlying embryonic developmental toxicity caused by benzo[a]pyrene in Japanese medaka (Oryzias latipes). (March 2020) - Yamaguchi, Akemi; Uchida, Masaya; Ishibashi, Hiroshi; Hirano, Masashi; Ichikawa, Nobuhiro; Arizono, Koji; Koyama, Jiro; Tominaga, Nobuaki
Abstract: Polycyclic aromatic hydrocarbons (PAHs), such as benzo[a]pyrene (BaP), are widely distributed in air, water, and sediments; however, limited data are available regarding their potential adverse effects on the early life stages of fish. In this study, we evaluated the embryonic teratogenicity and developmental toxicity of BaP in Japanese medaka ( Oryzias latipes ) using a nanosecond pulsed electric field (nsPEF) technique and predicted their molecular mechanisms via transcriptome analysis. The gas chromatography/mass spectrometry analyses revealed that the BaP was efficiently incorporated into the embryos by nsPEF treatment. The embryos incorporating BaP presented typical teratogenic and developmental effects, such as cardiovascular abnormalities, developmental abnormalities, and curvature of backbone. DNA microarray analysis revealed several unique upregulated genes, such as those involved in cardiovascular diseases, various cellular processes, and neural development. Furthermore, the gene set enrichment and network analyses found several genes and hub proteins involved in the developmental effects of BaP on the embryos. These findings suggest a potential mechanism of teratogenicity and developmental toxicity caused by exposure to BaP. The nsPEF and transcriptome analyses in combination can be effective for evaluating the potential effects of chemical substances on medaka embryos. Graphical abstract: Image 1 Highlights: The medaka embryos incorporating BaP revealed typical teratogenic and developmental effects. The gene expression analysis presented several genes and hub proteins involved in the developmental effects of BaP on medaka embryos. Our findings suggest a potential mechanism of teratogenicity and developmental toxicity caused by exposure to BaP.